Planting Environmentally Friendly Religiosity Awareness: PAI Learning Innovation Based on Mindfulness Eco Theological Perspective in SMPIT Sahabat Alam - U Abdullah Mu`min; Budi Munawar Khutomi; Azizi Abu Bakar (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2025)
This study aims to explore the innovation of Islamic Religious Education Learning (PAI) through the integration of mindfulness approach and eco-theological perspective in instilling awareness of environmentally friendly religiosity in students at SMPIT Sahabat Alam. This integration proceeds from the idea that spiritual awareness and ecological responsibility are complementary dimensions in forming reflective faith and concern for the preservation of nature. This research is motivated by the need for a PAI learning model that is not only oriented to cognitive aspects, but also fosters spiritual awareness that encourages ecological behavior. The research uses qualitative methods with case study design, through observation, in-depth interviews, and documentation of the PAI learning process at the school. The results showed that the application of mindfulness in PAI learning increased students ' focus, inner calm, and spiritual reflection on Qur'anic verses related to nature. The integration of eco-theological values reinforces the understanding that caring for the environment is part of the practice of faith and piety. The internalization of these values is reflected in the change in students ' attitudes towards cleanliness, appreciation for God's creation, as well as active participation in the activities of the school environment. Overall, awareness-based PAI learning with an eco-theological perspective has proven effective in instilling religiosity that blends with ecological responsibility. This Model offers a contextual, humanistic, and transformative Pai learning approach, and has the potential to be replicated in various Islamic education units to strengthen the spiritual-ecological character of the younger generation in the midst of a global environmental crisis.Keywords: eco-friendly religiosity, mindfulness, eco-theologis, PAI learning, educational innovation, SMPIT Sahabat Alam